The importance of the proximal resection margin distance for proximal gastric adenocarcinoma: A multi‐institutional study of the US Gastric Cancer Collaborative. Issue 2 (14th August 2015) - Postlewait, Lauren M.; Squires, Malcolm H.; Kooby, David A.; Poultsides, George A.; Weber, Sharon M.; Bloomston, Mark; Fields, Ryan C.; Pawlik, Timothy M.; Votanopoulos, Konstantinos I.; Schmidt, Carl R.; Ejaz, Aslam; Acher, Alexandra W.; et al.
<x xml:space="preserve">Abstract</x> Background A 5 cm margin is advocated for distal gastric adenocarcinoma (GAC). The optimal proximal resection margin (PM) length for proximal GAC is not established. Methods Patients who underwent curative‐intent resection for proximal GAC from 2000 to 2012 at 7 centers in the US Gastric Cancer Collaborative were included. PM length was sequentially dichotomized and analyzed at 0.5 cm increments (0.5–6.5 cm). Outcomes after negative margin (R0) and positive microscopic margin (R1) resections were compared. Primary endpoints were local recurrence (LR) and overall survival (OS). Results All patients (n = 162) had R0 distal margins. 151 (93.2%) had an R0‐PM with mean length of 2.6 cm (median:1.7 cm; range:0.1–15 cm). A greater PM distance was not associated with LR or OS. An R1‐PM was associated with higher N‐stage (N3:73% vs. 26%; P = 0.007) and increased LR (HR6.1; P = 0.009) but not associated with decreased OS. On multivariate analysis, an R1‐PM was also not independently associated with LR. Conclusions For resection of proximal gastric adenocarcinoma, proximal margin length is not associated with local recurrence or overall survival. An R1 margin is associated with advanced N‐stage but is not independently associated with recurrence or survival. When performing resection of proximal gastric adenocarcinoma, efforts to achieve a specific margin distance, especially if it necessitates an esophagectomy, should be abandoned. J. Surg. Oncol. 2015 111:203–207. © 2015 Wiley Periodicals, Inc.